Covalent organic framework / ionic liquid composite material as well as preparation method and application thereof

By combining the synthetic covalent organic framework/ionic liquid composite materials with PT-SPE technology, the problem of insufficient detection sensitivity and speed of bisphenols in the prior art is solved, and efficient and convenient detection of a variety of bisphenols is achieved.

CN119869474APending Publication Date: 2025-04-25LUOYANG INST OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510049152.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art detects a variety of bisphenol substances, and the sensitivity and speed are insufficient, and the selectivity of solid-phase extraction materials is not strong, making it difficult to meet the needs of efficient detection.

Method used

By synthesizing covalent organic framework/ionic liquid composite materials, combining Pickering emulsion polymerization method and solvothermal method, COFs materials with high specific surface area and stability were prepared, and combined with PT-SPE technology for simultaneous extraction of a variety of bisphenols.

Benefits of technology

The sensitivity and speed of the solid-phase extraction method are significantly improved, and the detection limit is as low as 0.06-0.40ng/L, enhancing the convenience of detection of a variety of bisphenol substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869474A_ABST
    Figure CN119869474A_ABST
Patent Text Reader

Abstract

The invention relates to a covalent organic framework / ionic liquid composite material and a preparation method and application thereof.The preparation method comprises the steps that firstly, through quaternization, part of chlorine atoms of polyether rubber are replaced with ionic liquid groups to prepare polyionic liquid, then part of remaining chlorine atoms on the polyionic liquid are replaced with sulfydryl, and then an alkenyl-containing COFs material is synthesized; and finally, dissolving the sulfydryl-containing polyionic liquid in trichloromethane, stirring, adding the alkenyl-containing COFs material and azodiisobutyronitrile, refluxing and stirring for 60 hours at 72 DEG C under the protection of nitrogen, cooling to room temperature, and centrifuging, washing and vacuum-drying the product to obtain orange powder, namely the covalent organic framework / ionic liquid composite material. The composite material is filled to prepare PT-SPE for simultaneous extraction of four bisphenol substances, the sensitivity of a solid-phase extraction method is greatly improved, the detection limit is as low as 0.06-0.40 ng / L, and the speed and convenience of the solid-phase extraction method are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material synthesis and sample pretreatment, in particular to a covalent organic framework / ionic liquid composite material and a preparation method and application thereof. Background Art

[0002] Bisphenols include bisphenol A, bisphenol F, bisphenol S, tetrabromobisphenol A, bisphenol AF, etc. With the development of industry, bisphenols are widely used in the production of polymer materials. Long-term exposure to low concentrations of bisphenols will affect many aspects of the human body, such as reproductive system, nervous system, embryonic development, etc., especially for infants and pregnant women and other high-risk sensitive groups. Therefore, the research on the detection method of bisphenols is of great significance. However, whether in environmental samples or biological samples, the content of bisphenols is relatively low and the matrix is ​​complex. Therefore, before using relevant instruments for content detection, sample pretreatment technology is needed to separate and enrich the target. Solid phase extraction technology is a sample pretreatment method based on solid-liquid separation and extraction, which has the advantages of low reagent consumption, high enrichment multiples, simple operation process, and low cost. Among many solid phase extraction devices, the Pipette Tip Solid Phase Extraction (PT-SPE) not only requires less sample volume and is suitable for the separation and enrichment of trace biological samples, but is also simple to operate, easy to carry, and has a faster detection speed, making it more suitable for on-site detection. The type and properties of the extraction material are the core of the solid phase extraction method, which directly determines its accuracy and sensitivity. At present, the commercial solid phase extraction materials used for the detection of bisphenols generally have low specificity and their selectivity needs to be improved. Covalent organic frameworks (COFs) are one of the solid phase extraction materials that are currently being widely studied. They have the advantages of large specific surface area, good stability, and many organic functional groups. They have great potential to become a high-sensitivity and good-selectivity solid phase extraction material.

[0003] In 2024, He et al. first used nano-silica as a stabilizer to prepare large-sized porous three-dimensional spherical polymers by Pickering emulsion polymerization, and then converted them into porous spherical three-dimensional COFs by solvothermal method. Such COFs present a uniform spherical morphology (15-45 μm) and a large specific surface area. This study used such COFs as dispersed solid phase extraction adsorbents and combined them with high performance liquid chromatography to determine BPF in water samples and orange juice, with a detection limit (S / N=3) of 0.1 ng / mL. Although the use of COFs materials for the extraction of bisphenols can improve the sensitivity of the method to a certain extent, most studies currently only stay at the dispersed extraction of a single bisphenol, and no research has been able to combine COFs materials with PT-SPE to give full play to the advantages of both and improve the sensitivity, speed and convenience of simultaneous detection of multiple bisphenols. Summary of the invention

[0004] In order to solve the above problems, the object of the present invention is to provide a covalent organic framework / ionic liquid composite material and a preparation method and application thereof, which specifically comprises the following steps:

[0005] (1) Synthesis of polyionic liquids

[0006] Weigh 2.50 g of chloroether rubber, dissolve it completely in chloroform, add 1-methylimidazole, heat and stir for 24 hours, then cool to room temperature, add lithium bis(trifluoromethanesulfonylimide), stir at room temperature for 48 hours, and after stirring, the viscous transparent liquid obtained is the polyionic liquid;

[0007] (2) Synthesis of thiol-containing polyionic liquids

[0008] 2.14 g of the polyionic liquid prepared in step (1) was taken and dissolved in chloroform, and then thiourea and a 95% by volume ethanol aqueous solution were added, and the mixture was stirred at 60° C. to 70° C. for 6 to 8 hours under the protection of nitrogen. Then, the system temperature was lowered to room temperature, and a 20% by mass NaOH aqueous solution was added, followed by stirring at room temperature for 2 hours. Finally, the mixed liquid obtained by stirring was washed with water until it was neutral to obtain a transparent viscous liquid, which was the thiol-containing polyionic liquid;

[0009] (3) Synthesis of olefin-containing COFs

[0010] 1,3,5-tri(4-aminophenyl)benzene, 2,5-dimethoxy-1,4-terephthalaldehyde and 2,5-divinyl-1,4-terephthalaldehyde are added to a three-necked flask respectively, and then 12-20 mL of mixed solvent A is added, wherein the mixed solvent A is obtained by mixing 1,4-dioxane and 1,3,5-trimethylbenzene, and then ultrasonicated for 5 minutes, and then 1.2-1.5 mL of 6 mol / L acetic acid aqueous solution is added, and then stirred at room temperature for 72 hours under nitrogen protection; after the stirring is completed, the stirred product is centrifuged, the upper liquid is discarded, the precipitate obtained by centrifugation is washed with methanol, and vacuum dried at 40°C for 12 hours, and the obtained yellow powder is the alkenyl-containing COFs material;

[0011] (4) Synthesis of covalent organic framework / ionic liquid composites

[0012] The thiol-containing polyionic liquid obtained in step (2) is dissolved in 100-150 mL of chloroform and magnetically stirred for 4 h. Then, the alkenyl-containing COFs material and azobisisobutyronitrile obtained in step (3) are added. Then, under nitrogen protection, the mixture is refluxed at 72° C. and stirred for 60 h. Finally, the temperature is lowered to room temperature, the product obtained after reflux is centrifuged, the upper liquid is discarded, and the precipitate obtained by centrifugation is washed with ethanol and vacuum dried to obtain an orange-yellow powder, which is a covalent organic framework / ionic liquid composite material, denoted as COFs-PILs.

[0013] Furthermore, in step (1), the amount of chloroform is 100-200 mL, the amount of 1-methylimidazole is 0.81-1.21 g (i.e., 9.878-14.775 mmol), and the amount of lithium bis(trifluoromethanesulfonyl)imide is 3.39-5.06 g.

[0014] Furthermore, after adding 1-methylimidazole in step (1), the temperature is raised to 85° C. to 90° C. and stirred at this temperature for 24 hours.

[0015] Furthermore, in step (2), the volumes of chloroform and ethanol aqueous solution are both 100 mL, the volume of NaOH aqueous solution is 200 mL, and the mass of thiourea is 0.21-0.41 g (i.e., the amount of substance is 2.698-5.395 mmol).

[0016] Furthermore, in step (3), the mass of 1,3,5-tri(4-aminophenyl)benzene is 0.3750 g (i.e., the amount of substance is 1.068 mmol), the mass of 2,5-dimethoxy-1,4-terephthalaldehyde is 0.0800-0.2320 g (i.e., 0.400-1.202 mmol), and the mass of 2,5-divinyl-1,4-terephthalaldehyde is 0.0744-0.2236 g (i.e., 0.400-1.202 mmol).

[0017] Furthermore, in step (3), the mixed solvent A is obtained by mixing 1,4-dioxane and 1,3,5-trimethylbenzene in a volume ratio of 1:1.

[0018] Furthermore, in step (4), the amount of the thiol-containing polyionic liquid is 0.3-0.4 g, the amount of the olefin-containing COFs material is 0.2-0.3 g, and the amount of azobisisobutyronitrile is 0.2-0.3 g (ie, 1.220-1.829 mmol).

[0019] The present invention also provides a covalent organic framework / ionic liquid composite material obtained according to the preparation method and its application in the simultaneous detection of multiple bisphenol substances.

[0020] The covalent organic framework / ionic liquid composite material is loaded into the pipette nozzle, and both ends of the nozzle are plugged with absorbent cotton to obtain a filled solid phase extraction nozzle. A syringe is connected to the upper end of the solid phase extraction nozzle, and a micro-injection pump is used to perform PT-SPE operation.

[0021] The invention first replaces part of the chlorine atoms of the polyether rubber with ionic liquid groups through a quaternization reaction to prepare a polyionic liquid, then replaces part of the remaining chlorine atoms on the polyionic liquid with thiol groups, then synthesizes an olefinic COFs material, finally dissolves the thiol-containing polyionic liquid in chloroform, stirs, adds the olefinic COFs material and azobisisobutyronitrile, then refluxes and stirs at 72°C for 60 hours under nitrogen protection, cools to room temperature, centrifuges the product, washes and vacuum-dries, and obtains an orange-yellow powder, which is a covalent organic framework / ionic liquid composite material.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention successfully bonds a covalent organic framework material with an ionic liquid to prepare a composite material, and uses the composite material for the simultaneous extraction of four bisphenols, greatly improving the sensitivity of the solid phase extraction method, with a detection limit as low as 0.06-0.40 ng / L.

[0024] (2) The present invention fills the prepared covalent organic framework / ionic liquid composite material into PT-SPE, which greatly improves the speed and convenience of the solid phase extraction method. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The electron scanning microscope image and Fourier transform infrared spectrum image of the covalent organic framework / ionic liquid composite material prepared in Example 1, wherein Figure A is an electron scanning microscope image and Figure B is a Fourier transform infrared spectrum image;

[0026] Figure 2It is a flow chart of the PT-SPE extraction device of the present invention;

[0027] Figure 3 It is the liquid chromatogram of the PT-SPE made of the covalent organic framework / ionic liquid composite material prepared in Example 1 before and after extraction of the spiked environmental water sample (the spiked concentration of the four bisphenols, bisphenol A, bisphenol AP, bisphenol AF, and bisphenol Z, are all 100 μg / L), wherein A is the chromatogram of the spiked environmental water sample before extraction (the spiked concentration of the four bisphenols are all 100 μg / L), and B is the chromatogram of the spiked environmental water sample after extraction (the spiked concentration of the four bisphenols are all 100 μg / L). DETAILED DESCRIPTION

[0028] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.

[0029] Embodiment 1:

[0030] (1) Synthesis of polyionic liquids

[0031] Weigh 2.50 g of chloroether rubber, dissolve it completely in 150 mL of chloroform, add 0.81 g (i.e., 9.878 mmol) of 1-methylimidazole, heat to 90° C., and stir at this temperature for 24 h, then cool to room temperature, add 3.39 g of lithium bis(trifluoromethanesulfonylimide), and stir at room temperature for 48 h. After stirring, the viscous transparent liquid obtained is a polyionic liquid with a chlorine content of 50%;

[0032] (2) Synthesis of thiol-containing polyionic liquids

[0033] Take 2.14 g of the polyionic liquid with a chlorine content of 50% prepared in step (1) and dissolve it in 100 mL of chloroform, then add 0.41 g (i.e. 5.395 mmol) of thiourea and 100 mL of 95% ethanol aqueous solution, and stir at 70°C for 8 h under the protection of nitrogen. Then, lower the system temperature to room temperature, add 200 mL of 20% NaOH aqueous solution, and then stir at room temperature for 2 h. Finally, wash the mixed liquid obtained by stirring with water until it is neutral, and obtain a transparent viscous liquid, which is a polyionic liquid with a thiol content of 50%;

[0034] (3) Synthesis of olefin-containing COFs

[0035] 0.3750 g (i.e., 1.068 mmol) of 1,3,5-tris(4-aminophenyl)benzene, 0.1550 g (i.e., 0.799 mmol) of 2,5-dimethoxy-1,4-terephthalaldehyde and 0.1500 g (i.e., 0.806 mmol) of 2,5-divinyl-1,4-terephthalaldehyde were added to a three-necked flask, and then 12 mL of a mixed solvent A was added, wherein the mixed solvent A was obtained by mixing 1,4-dioxane and 1,3,5-trimethylbenzene in a volume ratio of 1:1, and then ultrasonicated for 5 min to make the raw materials uniformly mixed, and then 1.2 mL of 6 mol / L acetic acid aqueous solution was added, and then stirred at room temperature for 72 h under nitrogen protection; after the stirring was completed, the product obtained by stirring was centrifuged, the upper layer of liquid was discarded, the precipitate obtained by centrifugation was washed with methanol to remove impurities, and vacuum dried at 40°C for 12 h, and the obtained yellow powder was the COFs material with an alkenyl content of 50%;

[0036] (4) Synthesis of COFs-PILs

[0037] 0.3940 g of the polyionic liquid with a thiol content of 50% obtained in step (2) was dissolved in 150 mL of chloroform and magnetically stirred for 4 h to completely dissolve it. Then, 0.2570 g of the COFs material with an alkenyl content of 50% obtained in step (3) and 0.2000 g (i.e., 1.220 mmol) of azobisisobutyronitrile were added. Then, under nitrogen protection, the mixture was refluxed and stirred at 72° C. for 60 h. Finally, the temperature was lowered to room temperature, the product obtained after reflux was centrifuged, the upper liquid was discarded, and the precipitate obtained by centrifugation was washed with ethanol and vacuum dried to obtain an orange-yellow powder, which was a covalent organic framework / ionic liquid composite material, denoted as COFs-PILs.

[0038] Figure 1 Figure A, i.e., the electron scanning microscopy characterization results, shows that the COFs-PILs prepared in Example 1 are regular spheres with a particle size of about 500 nm, and the spherical surface has obvious flaky or petal-like structures. Figure 1 Figure B, the Fourier infrared spectrum, shows that 3024cm -1 The peak at 1618 cm is the CH stretching vibration peak of the benzene ring on COFs. -1 The peak at 1591-1463 cm is the stretching vibration peak of C=N on COFs. -1 The peak at 1637cm belongs to the skeleton vibration absorption peak of the benzene ring on COFs. -1 The peak at is the skeleton vibration peak of the imidazole ring on the ionic liquid. Therefore, there are indeed COFs groups and ionic liquid groups on COFs-PILs.

[0039] Embodiment 2:

[0040] (1) Synthesis of polyionic liquids

[0041] Weigh 2.50 g of chloroether rubber, dissolve it completely in 200 mL of chloroform, add 1.21 g (i.e., 14.775 mmol) of 1-methylimidazole, heat to 90° C., and stir at this temperature for 24 h, then cool to room temperature, add 5.06 g of lithium bis(trifluoromethanesulfonylimide), and stir at room temperature for 48 h. After stirring, the viscous transparent liquid obtained is a polyionic liquid with a chlorine content of 24.1%;

[0042] (2) Synthesis of thiol-containing polyionic liquids

[0043] Take 2.14 g of the polyionic liquid with a chlorine content of 24.1% prepared in step (1) and dissolve it in 100 mL of chloroform, then add 0.21 g (i.e. 2.698 mmol) of thiourea and 100 mL of 95% ethanol aqueous solution, and stir at 65°C for 6 hours under the protection of nitrogen. Then, lower the system temperature to room temperature, add 200 mL of 20% NaOH aqueous solution, and then stir at room temperature for 2 hours. Finally, wash the mixed liquid obtained by stirring with water until it is neutral, and obtain a transparent viscous liquid, which is a polyionic liquid with a thiol content of 24.1%;

[0044] (3) Synthesis of olefin-containing COFs

[0045] 0.3750 g (i.e. 1.068 mmol) of 1,3,5-tris(4-aminophenyl)benzene, 0.2320 g (i.e. 1.202 mmol) of 2,5-dimethoxy-1,4-terephthalaldehyde and 0.0744 g (i.e. 0.400 mmol) of 2,5-divinyl-1,4-terephthalaldehyde were added to a three-necked flask, and then 15 mL of a mixed solvent A was added, wherein the mixed solvent A was obtained by mixing 1,4-dioxane and 1,3,5-trimethylbenzene in a volume ratio of 1:1, and then ultrasonicated for 5 min to make the raw materials uniformly mixed, and then 1.5 mL of 6 mol / L acetic acid aqueous solution was added, and then stirred at room temperature for 72 h under nitrogen protection; after the stirring was completed, the product obtained by stirring was centrifuged, the upper layer of liquid was discarded, the precipitate obtained by centrifugation was washed with methanol to remove impurities, and vacuum dried at 40°C for 12 h, and the obtained yellow powder was the COFs material with an alkenyl content of 25%;

[0046] (4) Synthesis of COFs-PILs

[0047] 0.3524 g of the polyionic liquid with a thiol content of 24.1% obtained in step (2) was dissolved in 150 mL of chloroform and magnetically stirred for 4 h to completely dissolve it. Then, 0.2050 g of the COFs material with an alkenyl content of 25% obtained in step (3) and 0.2000 g (i.e., 1.220 mmol) of azobisisobutyronitrile were added. Then, under nitrogen protection, the mixture was refluxed and stirred at 72° C. for 60 h. Finally, the temperature was lowered to room temperature, the product obtained after reflux was centrifuged, the upper liquid was discarded, and the precipitate obtained by centrifugation was washed with ethanol and vacuum dried to obtain an orange-yellow powder, which was a covalent organic framework / ionic liquid composite material, denoted as COFs-PILs.

[0048] Embodiment 3:

[0049] (1) Synthesis of polyionic liquids

[0050] Weigh 2.50 g of chloroether rubber, dissolve it completely in 200 mL of chloroform, add 1.00 g (i.e. 12.195 mmol) of 1-methylimidazole, heat to 90° C., and stir at this temperature for 24 h, then cool to room temperature, add 4.23 g of lithium bis(trifluoromethanesulfonylimide), and stir at room temperature for 48 h. After stirring, the viscous transparent liquid obtained is a polyionic liquid with a chlorine content of 37.4%;

[0051] (2) Synthesis of thiol-containing polyionic liquids

[0052] Take 2.14 g of the polyionic liquid with a chlorine content of 37.4% prepared in step (1) and dissolve it in 100 mL of chloroform, then add 0.31 g (i.e. 4.047 mmol) of thiourea and 100 mL of 95% ethanol aqueous solution, and stir at 70°C for 7 hours under the protection of nitrogen. Then, lower the system temperature to room temperature, add 200 mL of 20% NaOH aqueous solution, and then stir at room temperature for 2 hours. Finally, wash the mixed liquid obtained by stirring with water until it is neutral, and obtain a transparent viscous liquid, which is a polyionic liquid with a thiol content of 37.4%;

[0053] (3) Synthesis of olefin-containing COFs

[0054] 0.3750 g (i.e., 1.068 mmol) of 1,3,5-tris(4-aminophenyl)benzene, 0.0800 g (i.e., 0.400 mmol) of 2,5-dimethoxy-1,4-terephthalaldehyde and 0.2236 g (i.e., 1.202 mmol) of 2,5-divinyl-1,4-terephthalaldehyde were added to a three-necked flask, and then 12 mL of a mixed solvent A was added, wherein the mixed solvent A was obtained by mixing 1,4-dioxane and 1,3,5-trimethylbenzene in a volume ratio of 1:1, and then ultrasonicated for 5 min to make the raw materials uniformly mixed, and then 1.2 mL of 6 mol / L acetic acid aqueous solution was added, and then stirred at room temperature for 72 h under nitrogen protection; after the stirring was completed, the product obtained by stirring was centrifuged, the upper layer of liquid was discarded, the precipitate obtained by centrifugation was washed with methanol to remove impurities, and vacuum dried at 40°C for 12 h, and the obtained yellow powder was the COFs material with an alkenyl content of 75%;

[0055] (4) Synthesis of COFs-PILs

[0056] 0.3036 g of the polyionic liquid with a thiol content of 37.4% obtained in step (2) was dissolved in 125 mL of chloroform and magnetically stirred for 4 h to completely dissolve it. Then, 0.2068 g of the COFs material with an alkenyl content of 75% obtained in step (3) and 0.2000 g (i.e., 1.220 mmol) of azobisisobutyronitrile were added. Then, under nitrogen protection, the mixture was refluxed and stirred at 72° C. for 60 h. Finally, the temperature was lowered to room temperature, the product obtained after reflux was centrifuged, the upper liquid was discarded, and the precipitate obtained by centrifugation was washed with ethanol and vacuum dried to obtain an orange-yellow powder, which was a covalent organic framework / ionic liquid composite material, denoted as COFs-PILs.

[0057] Application examples:

[0058] Separation and enrichment of bisphenols using the COFs-PILs prepared in Example 1 as an adsorbent:

[0059] 0.4 mg of COFs-PILs prepared in Example 1 was loaded into a 200 μL pipette nozzle, and both ends of the nozzle were plugged with absorbent cotton to obtain a filled solid phase extraction nozzle. A 5 mL syringe was connected to the upper end of the solid phase extraction nozzle, and PT-SPE operation was performed with the help of a microinjection pump (such as Figure 2As shown): First, 5 mL of methanol and 5 mL of water were passed through the solid phase extraction nozzle to activate the adsorbent; then, sodium chloride was added to 5 mL of the spiked environmental water sample to make its concentration 0.050 mol / L, and the pH was adjusted to 6. The sample solution was loaded into a syringe and passed through the solid phase extraction nozzle at a flow rate of 500 μL / min; finally, 0.1 mL of methanol was used as an eluent to elute the bisphenol target from the adsorbent and the eluate was collected, filtered with a 0.22 μm filter, and then analyzed by high performance liquid chromatography. When the concentrations of the four bisphenols in the spiked environmental water sample were all 100 μg / L, the chromatograms before and after extraction were shown in Figure 1. Figure 3 ,from Figure 3 It can be seen that after PT-SPE operation, the four bisphenols were enriched to a great extent.

[0060] The analytical performance of the method was evaluated in terms of linear range, detection limit, and quantification limit, and the results are shown in Table 1.

[0061] Table 1. Method evaluation of solid phase extraction methods

[0062]

[0063] As shown in Table 1, the PT-SPE method with COFs-PILs as adsorbent has a good linear relationship in a very wide range. 2 The values ​​were all greater than 0.995. The detection limit and quantification limit calculated according to the signal-to-noise ratio (S / N=3) and signal-to-noise ratio (S / N=10) were 0.06-0.40 ng / L and 0.20-2.0 ng / L, respectively. These results show that the PT-SPE method based on COFs-PILs has a wide linear range and high sensitivity.

[0064] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a covalent organic framework / ionic liquid composite material, characterized in that: The specific steps include: (1) Synthesis of polyionic liquids Weigh 2.50 g of chloroether rubber, dissolve it completely in chloroform, add 1-methylimidazole, heat and stir for 24 hours, then cool to room temperature, add lithium bis(trifluoromethanesulfonylimide), stir at room temperature for 48 hours, and after stirring, the viscous transparent liquid obtained is the polyionic liquid; (2) Synthesis of thiol-containing polyionic liquids 2.14 g of the polyionic liquid prepared in step (1) was taken and dissolved in chloroform, and then thiourea and a 95% by volume ethanol aqueous solution were added, and the mixture was stirred at 60° C. to 70° C. for 6 to 8 hours under the protection of nitrogen. Then, the system temperature was lowered to room temperature, and a 20% by mass NaOH aqueous solution was added, followed by stirring at room temperature for 2 hours. Finally, the mixed liquid obtained by stirring was washed with water until it was neutral to obtain a transparent viscous liquid, which was the thiol-containing polyionic liquid; (3) Synthesis of olefin-containing COFs 1,3,5-tri(4-aminophenyl)benzene, 2,5-dimethoxy-1,4-terephthalaldehyde and 2,5-divinyl-1,4-terephthalaldehyde are added to a three-necked flask respectively, and then 12-20 mL of mixed solvent A is added, wherein the mixed solvent A is obtained by mixing 1,4-dioxane and 1,3,5-trimethylbenzene, and then ultrasonicated for 5 minutes, and then 1.2-1.5 mL of 6 mol / L acetic acid aqueous solution is added, and then stirred at room temperature for 72 hours under nitrogen protection; after the stirring is completed, the obtained product is centrifuged, the upper layer of liquid is discarded, and the precipitate obtained by centrifugation is washed with methanol, and vacuum dried at 40°C for 12 hours, and the obtained yellow powder is the alkenyl-containing COFs material; (4) Synthesis of covalent organic framework / ionic liquid composites The thiol-containing polyionic liquid obtained in step (2) is dissolved in 100-150 mL of chloroform and magnetically stirred for 4 h. Then, the alkenyl-containing COFs material and azobisisobutyronitrile obtained in step (3) are added. Then, under nitrogen protection, the mixture is refluxed at 72° C. and stirred for 60 h. Finally, the temperature is lowered to room temperature, the product obtained after reflux is centrifuged, the upper liquid is discarded, and the precipitate obtained by centrifugation is washed with ethanol and vacuum dried to obtain an orange-yellow powder, which is a covalent organic framework / ionic liquid composite material, denoted as COFs-PILs.

2. The method for preparing the covalent organic framework / ionic liquid composite material according to claim 1, characterized in that: In step (1), the amount of chloroform is 100-200 mL, the amount of 1-methylimidazole is 0.81-1.21 g, and the amount of lithium bis(trifluoromethanesulfonyl)imide is 3.39-5.06 g.

3. The method for preparing the covalent organic framework / ionic liquid composite material according to claim 1, characterized in that: After adding 1-methylimidazole in step (1), the temperature is raised to 85° C. to 90° C. and stirred at this temperature for 24 h.

4. The method for preparing the covalent organic framework / ionic liquid composite material according to claim 1, characterized in that: In step (2), the volumes of chloroform and ethanol aqueous solution are both 100 mL, the volume of NaOH aqueous solution is 200 mL, and the mass of thiourea is 0.21-0.41 g.

5. The method for preparing the covalent organic framework / ionic liquid composite material according to claim 1, characterized in that: In step (3), the mass of 1,3,5-tri(4-aminophenyl)benzene is 0.3750 g, the mass of 2,5-dimethoxy-1,4-terephthalaldehyde is 0.0800-0.2320 g, and the mass of 2,5-divinyl-1,4-terephthalaldehyde is 0.0744-0.2236 g.

6. The method for preparing the covalent organic framework / ionic liquid composite material according to claim 1, characterized in that: In step (3), the mixed solvent A is obtained by mixing 1,4-dioxane and 1,3,5-trimethylbenzene in a volume ratio of 1:

1.

7. The method for preparing the covalent organic framework / ionic liquid composite material according to claim 1, characterized in that: In step (4), the amount of the thiol-containing polyionic liquid is 0.3-0.4 g, the amount of the olefin-containing COFs material is 0.2-0.3 g, and the amount of azobisisobutyronitrile is 0.2-0.3 g.

8. A covalent organic framework / ionic liquid composite material prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the covalent organic framework / ionic liquid composite material as claimed in claim 8 in the simultaneous detection of multiple bisphenols.

10. The use according to claim 9, characterized in that The covalent organic framework / ionic liquid composite material is loaded into the pipette nozzle, and both ends of the nozzle are blocked with absorbent cotton to obtain a filled solid phase extraction nozzle. A syringe is connected to the upper end of the solid phase extraction nozzle, and PT-SPE operation is performed with the help of a micro-injection pump.

Citation Information

Cited By

  • Flame-retardant high-wear-resistance modified polyolefin material, preparation method thereof and valve

    CN121271079A

  • Preparation method and application of ionic liquid bonded covalent organic framework material

    CN122234308A